Dissociation of MIF‐rpS3 Complex and Sequential NF‐κB Activation Is Involved in IR‐Induced Metastatic Conversion of NSCLC. Issue 11 (9th September 2015) - Youn, HyeSook; Son, Beomseok; Kim, Wanyeon; Jun, Se Young; Lee, Jung Sub; Lee, Jae‐Myung; Kang, ChulHee; Kim, Joon; Youn, BuHyun
ABSTRACT: Frequent relapse and spreading of tumors during radiotherapy are principal obstacles to treatment of non‐small cell lung cancer (NSCLC). In this study, we aimed to investigate how macrophage migration inhibitory factor (MIF) which is expressed at high levels in metastatic and primary lung cancer cells could regulate NSCLC metastasis in response to ionizing radiation (IR). The results indicated that MIF and ribosomal protein S3 (rpS3) were shown to be connected to inflammation, proliferation, and metastasis of NSCLC via IR‐induced activation of the NF‐κB pathway. Under unirradiated conditions, MIF physically established a complex with rpS3. MIF‐rpS3 dissociation induced by IR activated NF‐κB and made the expression of target genes of this factor transactivated in two NSCLC cell lines, A549, and NCI‐H358. We also found that IR‐induced dissociation of this complex led to increased secretion of pro‐inflammatory cytokines and modulated the expression of epithelial–mesenchymal transition marker proteins. Finally, the effects of IR‐induced dissociation of the MIF‐rpS3 complex on tumor metastasis were confirmed by in vivo xenograft studies. Taken together, the present study revealed that dissociation of the MIF‐rpS3 complex and subsequent activation of NF‐κB is a critical post‐IR exposure event that accounts for IR‐induced metastatic conversion of NSCLC. J. Cell. Biochem. 116: 2504–2516, 2015. © 2015 Wiley Periodicals, Inc.